Synthesis and Complexation of Nitrogen-rich Materials - Sebastiao, Elena (Université d'Ottawa / University of Ottawa, 2015)
Nitrogen-rich materials are of increasing interests for the development of a wide variety of applications. These compounds are prime candidates for ligands used in the complexation of metals since they possess several lone pairs. Resulting complexes have also exhibited a wide variety of interesting properties, ranging from magnetism to gas absorption to energetic properties. This thesis describes the synthesis and characterisation of new metallic complexes with the known energetic ligands: hydrazine and H3bta, as well as that of a new nitrogen-rich compound: H4ttp. Chapter 2 outlines a series of chains bridged by hydrazine and their potential as initiatory compounds. Mononuclear lanthanide H3bta complexes are presented in Chapter 3. The development of the new nitrogen-rich, tetrazole-based H4ttp ligand is described in Chapter 4. This new ligand was used to synthesise various lanthanide complexes through hydrothermal reactions.
Keywords: nitrogen-rich; bta; ttp; tetrazole